The evolution of international arbitration : judicialization, governance, legitimacy - Stone Sweet, Alec; Grisel, Florian, 1982- (Oxford : Oxford University Press, 2017)
The development of international arbitration as an autonomous legal order is one of the most remarkable stories of institution building at the global level over the past century. Today, transnational firms and states settle their most important commercial and investment disputes not in courts, but in arbitral centres, a tightly networked set of organisations that compete with one another for docket, resources and influence. In this work, Alec Stone Sweet and Florian Grisel show that international arbitration has undergone a self-sustaining process of institutional evolution that has steadily enhanced arbitral authority.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 22, 2017).
Keywords: Arbitration (International law); Law; International law